ANALISIS PENGGUNAAN DIKSI PADA PASAL 480 TENTANG POLEMIK RANCANGAN UNDANG-UNDANG KUHP (RUU KUHP) DI INDONESIA - Ririn Indraswari (Jurnal Ilmiah Pranata Edu, 2019)
The rejection of the RKUHP is voiced throughout the country. In the demands of students, the RKUHP was canceled. The emergence of RKUHP became a controversy so there was a lot of resistance from the community. One of the bills is expanding the definition of rape. In RKUHP, rape occurs as long as there is male to female violence. "Including rape and criminal offenses as referred to in paragraph (1) includes acts of: a. Intercourse with someone with his consent, because the person believes that the person is a legitimate husband / wife". Thus reads Article 480 paragraph 2 ". That definition, a husband can rape his wife. With the condition that the wife does not want to have intercourse and the husband will use violence When compared to the Criminal Code used today, there has been a shift in the definition of rape. Because, "rape" in the RKUHP can be done by a legitimate partner. While in the Penal Code, rape occurs when the perpetrators and victims are not bound by marriage. The method used is the use of diction in the written language. Formulation of the problem 1) How is the husband and wife's response to the polemic of RKUHP article 480. 2) How is the use of the rape diction in the Law? The results of the study can be concluded that, the responses of some respondents with the status of husband and wife are not supportive of the ratification of the Act, because there is no word of rape in marital ties, and has been regulated by the law on sexual violence in the household. The use of diction section article 480 in terms of accuracy, accuracy, harmony is not fully applied to the criteria for using diction. In the controversy article 480 verse 2 that uses the word multi-interpretation it should be reviewed. The word rape, including the popular diction, is inappropriate for article 480 paragraph 2. According to the government RKUHP article 480 paragraph 2 is an article that protects women. But the reader's point of view, in the relationship of husband and wife there is no term raping.